Effects of Spousal Separation and Internal Migration on Modern Contraceptive Use in Nepal: Evidence from the 2022 NDHS - Tiwari, Pradip Raj; Dhungana, Govinda Prasad (BMC Journal of Scientific Research, 2025)
Spousal separation by male out-migration and women’s own migration may influence access to and use of modern contraception. This study examines the effects of spousal separation and women’s internal migration on the use of modern contraceptives in Nepal. This study utilized cross-sectional data from the 2022 Nepal Demographic and Health Survey (NDHS). Descriptive statistics were used to estimate prevalence, and multivariate logistic regression models were employed to assess the association between migration status and modern contraceptive use, controlling for socio demographic covariates. Descriptive analysis revealed a substantial disparity in modern contraceptive use among non-migrant wives (62.4%) compared to left-behind wives (27.6%). Multivariate analysis confirmed that left-behind wives were significantly less likely to use modern contraception than non migrant wives (AOR=0.21, 95% CI: 0.18–0.23, p < 0.001). Women’s internal migration status and stream also influenced modern contraception use. Women migrating from urban-to urban (AOR = 0.80, 95% CI = 0.55-0.98) and rural-to-urban (AOR = 0.85, 95% CI = 0.74-0.99) areas had lower odds of contraceptive use compared to those migrating from rural-to-rural areas. However, internal migration did not significantly affect contraceptive use among left-behind wives, suggesting that spousal separation plays a more dominant role than women’s own mobility. These findings add to our understanding of how women’s and their husbands’ migration status influences the use of modern contraception. These findings suggest that family planning programs should address migration issues, target the needs of migrant couples, and increase access for women left behind during spousal return.